Pengaruh Lama Pemanasan dan Jenis Bahan Pangan Terhadap Mutu Minyak Goreng Sawit - Ganda R Ritonga; Rina Rismaya (Universitas Pattimura, 2025)
Prolonged and repeated use of cooking oil during frying leads to a deterioration in its quality due to various chemical reactions. The rate of quality degradation is influenced by the type of food being fried, as different ingredients contain varying compounds that interact with the oil. This study aimed to determine the effects of heating time and food type on the physicochemical quality parameters of cooking oil during frying. A 3x2 Factorial Completely Randomized Design was employed, with heating times of 5, 10, and 15 minutes, and two food types: shrimp crackers and salted fish. The parameters assessed included color, free fatty acids, iodine number, and moisture content. This study was conducted in duplicate with two replications per treatment. The results showed that both heating time and food type significantly affected oil degradation. Increased heating time and type of food being fried led to higher values of red and yellow coloration, moisture content, and free fatty acid levels, while the iodine value decreased, indicating increased oxidation. Heating time did not significantly affect the red color of cooking oil used for frying, and food type did not significantly influence changes in the iodine value. Overall, extended heating and the use of salted fish accelerated the degradation of cooking oil quality more than shrimp crackers, except in terms of iodine value. These findings highlight the importance of monitoring frying duration and food type to maintain oil quality, and can guide consumers and food businesses in establishing safe reuse limits for cooking oil.